Automação e robótica nas indústrias brasileiras: um estudo exploratório - Gomes, Bruno Souza (2004)
The Automation and the process of Robotization come, each come more, becoming guideline in the quarrels of hundreds of Brazilian industries, where the clear and identified trend is investments in the improvement of processes and the products, for intermediary of these technologies; with focus, that always possible, in the equipment nationalization. The present work has as objective to argue the model considered for Paul Kennedy (1993) with relation to the trend of Automation and Robotics in the World-wide Industries, analyzing the study carried through ahead of an emergent economy as the Brazilian. For in such a way, companies in Brazil had been searched, in different industrial segments, the state of the art in terms of automation technology and applied robotics the industrial processes, and suggested a different model of the idealized one originally for Kennedy. The analysis of the author based on the theorem that, in the discrete mathematics, we call 'law of the excluded middle', or either, according to Kennedy, Brazil would be living today a gradual migration of the industries for the rich countries. Brazil is an example of industrialized country, of emergent economy, that it intensely invests in automatized processes, but that it is not classified inside of the group of these rich countries. Through the carried through research a new model will be presented, in the which emergent countries as Brazil has access to the technology of tip in automation and robotics, applying the same one in its industrial processes.